Sudan Agriculture Value Chain Analysis - World Bank (World Bank, Washington, DC, 2020)
The new reform-oriented transitional government, formed on August 20, 2019, creates a unique window of opportunity in Sudan to spur economic growth, rebuilding and resilience. The general framework for the program of transitional government adopted in December 2019 sets out ten priorities for the government. One of these priorities is focused on addressing the economic crises and establishing the bases of sustainable development and includes, amongst others developing and promoting productive sectors. The purpose of this study, therefore, is to provide a road map to develop and promote agriculture and livestock sectors as an important part of the government’s priority of addressing the economic crises and establishing the bases of sustainable development.